Prevalence of Peri-Implantitis in Implants with Turned and Rough Surfaces: a Systematic Review - Nikola Saulacic; Benoit Schaller (eJournal of Oral Maxillofacial Research, 2019)
Objectives: Moderately-rough implant surface may improve implant therapy in terms of bone integration, but the increased surface roughness might affect the initiation and development of peri-implantitis. The aim of the present review was to compare the prevalence of peri-implantitis in implants with rough and turned (machined) implant surfaces.